Introduction to the Special Collection on The new roles of women and men and implications for families and societies - Livia Sz. Oláh; Rudolf Richter; Irena Kotowska (Demographic Research, 2023)
Background: This is the introduction to a special collection of articles produced within a large-scale collaborative research project, FamiliesAndSocieties, funded by the European Union's Seventh Framework Programme in 2013‒2017. Objective: The special collection addresses (1) the gendered outcomes of employment for fertility, well-being, and partnership stability, and (2) the new role of men in various socioeconomic positions and its implications for family life. Methods: International micro-level datasets (ESS, GGS) are analyzed in two comparative studies, while four country-case studies rely on country-specific datasets. The Swedish study also involves analyses of interview narratives of parental couples. Contribution: The articles highlight the evolving importance of economic uncertainty in fertility decisions and well-being, especially as related to limited changes in the role of breadwinner for men, and the role of policy context for women, including regarding links between women's employment and divorce. The results indicate that women have entered the public sphere to stay, but this only strengthens families if accompanied by relevant policy support. Renewed ideals of mothers being the primary carers of their children are found to hinder the realization of new fatherhood aspirations, while a clear socioeconomic gradient in men's family involvement in both first and post-divorce relationships may further enhance social inequalities.